2006
DOI: 10.1128/aac.00456-06
|View full text |Cite
|
Sign up to set email alerts
|

Complete Nucleotide Sequence of pK245, a 98-Kilobase Plasmid Conferring Quinolone Resistance and Extended-Spectrum-β-Lactamase Activity in a Clinical Klebsiella pneumoniae Isolate

Abstract: A plasmid containing the qnrS quinolone resistance determinant and the gene encoding the SHV-2 ␤-lactamase has been discovered from a clinical Klebsiella pneumoniae strain isolated in Taiwan. The complete 98-kb sequence of this plasmid, designated pK245, was determined by using a whole-genome shotgun approach. Transfer of pK245 conferred low-level resistance to fluoroquinolones in electroporant Escherichia coli epi300. The sequence of the immediate region surrounding qnrS in pK245 is nearly identical (>99% ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
65
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 47 publications
6
65
0
3
Order By: Relevance
“…The high prevalence of AAC(6=)-Ib is likely explained by the fact that the vast majority of our carbapenem-resistant K. pneumoniae isolates possessed ESBLs, as genes for AAC(6=)-Ib and ESBLs are known to localize to the same plasmid (32,33). In general keeping with our findings, previous studies have reported that AAC(6=)-Ib affects tobramycin and amikacin susceptibility, while sparing gentamicin (34).…”
Section: Discussionsupporting
confidence: 87%
“…The high prevalence of AAC(6=)-Ib is likely explained by the fact that the vast majority of our carbapenem-resistant K. pneumoniae isolates possessed ESBLs, as genes for AAC(6=)-Ib and ESBLs are known to localize to the same plasmid (32,33). In general keeping with our findings, previous studies have reported that AAC(6=)-Ib affects tobramycin and amikacin susceptibility, while sparing gentamicin (34).…”
Section: Discussionsupporting
confidence: 87%
“…The qnrS1 gene has been identifi ed now from several enterobacterial isolates from Japan (9), Germany (28), the United Kingdom (29), the United States (25), France (17), Vietnam (30), Taiwan (31,32), and Denmark (33). The qnrS2 gene (92% amino acid identity with QnrS1) was identifi ed from a transferable IncQ-related plasmid (pGNB2) isolated from an activated sludge bacterial community of a wastewater treatment plant in Germany (24) and in a single non-Typhi Salmonella clinical isolate from the United States (25).…”
Section: Discussionmentioning
confidence: 99%
“…Güven Ö (27) , sağlıklı çocukların dışkılarında kinolon dirençli E. coli taşıyıcılığı ve direnç mekanizmalarını saptamak amacıyla yaptığı araştırmada, kinolon direnci saptadığı 15 E. coli izolatında qnr geni saptamamıştır. Avrupa'daki çalışmalarda (31,33,45) , genellikle qnrS ve qnrB genleri baskın görülmekle birlikte, İngiltere'de yapılmış olan bir çalışmada (46) , qnrA geni, İspanya'da yapılmış olan bir çalışmada (36) ise, qnrA1 geni yüksek oranda belirlenmiştir. Türkiye'de E. coli ve Klebsiella spp.…”
Section: Discussionunclassified